Actinomycetes associated with hymenopteran insects: a promising source of bioactive natural products - Diarra, Umar; Osborne-Naikatini, Tamara; Subramani, Ramesh (Frontiers in Microbiology, 2024)
In recent years, the insect microbiome has become the focus of many actinomycete researchers in their search for novel bioactive compounds with members of the order Hymenoptera at the forefront of the revolution. Hymenoptera encompasses all bees, wasps, ants, and sawflies and is the third largest insect order by species richness. Additionally, Hymenoptera is the most diverse insect order in terms of ecological roles, behaviors, and social systems, thus making it an ideal starting point in the search for symbiotic actinomycetes. The aim of this review is to summarize current knowledge on hymenopteran associations with actinomycetes including information on interactions between actinomycetes and hymenopterans, isolation, and screening methodologies, as well as novel actinomycete species and natural products discovered between early 2013 and 2023. A total of 19 new species were discovered within this time period, with the genus Streptomyces being represented by 11 species while the remaining 8 belonged to rare actinomycetes genera. In addition, 35 novel compounds were reported from hymenopteranassociated actinomycetes within the same time period with the majority originating from Streptomyces strains. The reported novel compounds exhibit a range of biological activities including antibacterial, antifungal, anticancer, anti-enzymatic, and antiproliferative activity, as well as cytotoxicity.